2021
DOI: 10.1007/s10840-021-00952-w
|View full text |Cite
|
Sign up to set email alerts
|

Rebooting atrial fibrillation ablation in the COVID-19 pandemic

Abstract: Purpose Catheter ablation procedures for atrial fibrillation (AF) were significantly curtailed during the peak of coronavirus disease 2019 (COVID-19) pandemic to conserve healthcare resources and limit exposure. There is little data regarding periprocedural outcomes of medical procedures during the COVID-19 pandemic. We enacted protocols to safely reboot AF ablation while limiting healthcare resource utilization. We aimed to evaluate acute and subacute outcomes of protocols instituted for reboot of AF ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Six (26.1%) studies reported an inverse relationship between rising COVID-19 cases and the declining rates of EP procedures 11 , 17 20 , 27 . Organizational restructuring in response to the pandemic and the issuance of new guidelines for EP procedures were reported in nine (39.1%) studies 4 , 10 , 14 17 , 19 , 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six (26.1%) studies reported an inverse relationship between rising COVID-19 cases and the declining rates of EP procedures 11 , 17 20 , 27 . Organizational restructuring in response to the pandemic and the issuance of new guidelines for EP procedures were reported in nine (39.1%) studies 4 , 10 , 14 17 , 19 , 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Strict adherence to COVID-19 protocols can prevent postprocedural COVID-19 infections in both patients and staff amidst marked local COVID-19 prevalence. The practice of postprocedural same-day discharge wherever possible and virtual follow-up decreases the duration of hospital stays and provides adequate care to patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of preoperative practices (transesophageal echocardiography) and acute procedural outcomes of catheter ablation during and before COVID-19 pandemic revealed lesser rate of COVID-19 transmission, reduced complication rate and higher same day discharges in the 2020 cohort compared to 2019 cohort. These findings emphasize that complex electrophysiological procedures can be safety administered to high-risk COVID-19 patients with atrial fibrillation results in optimal clinical outcomes while maintaining the quality of care [ 67 ]. Analysis of 269 patients who underwent catheter ablation for arrhythmia in COVID-19 patients from January 1, 2020, to March 24, 2020, revealed arrhythmia-free survival in 95.9% patients, no COVID-19 infections reported during brief hospitalization period (3–5 days), and no COVID-19 infections during 3-month follow-up [ 68 ].…”
Section: Main Textmentioning
confidence: 99%
“…Increased utilization of catheter ablation in recent years and decreased procedural volumes during the COVID-19 pandemic further motivated this work. 14–16 Moreover, the consequences of such delays in catheter ablation for AF patients in terms of adverse events during the wait-period have not been studied.…”
Section: Introductionmentioning
confidence: 99%